A Glimpse of “Dicer Biology” Through the Structural and Functional Perspective - Paturi, Sneha; Deshmukh, Mandar V. (Frontiers in Molecular Biosciences, 2021)
The RNA interference pathway (RNAi) is executed by two core enzymes, Dicer and Argonaute, for accomplishing a tailored transcriptional and post-transcriptional gene regulation. Dicer, an RNase III enzyme, initiates the RNAi pathway, plays a pivotal role in fighting infection against pathogens, and acts as a housekeeping enzyme for cellular homeostasis. Here, we review structure-based functional insights of Dicer and its domains present in a diverse group of organisms. Although Dicer and its domains are evolutionarily conserved from microsporidian parasites to humans, recent cryo-electron microscopy structures of Homo sapiens Dicer and Drosophila melanogaster Dicer-2 suggest characteristic variations in the mechanism of the dsRNA substrate recognition. Interestingly, the necessity for more than one functionally distinct Dicer paralogs in insects and plants compared to a single Dicer in other eukaryotic life forms imply Dicer’s role in the interplay of RNAi and other defense mechanisms. Based on the structural and mechanistic information obtained during the last decade, we aim to highlight the significance of key Dicer domains that are crucial for Dicer specific recognition and precise cleavage of dsRNA substrates. Further, the role of Dicer in the formation of Argonaute based RNA-induced silencing complex (RISC) assembly formation, Dicer’s ability to regulate complex protein interaction network and its role in other cellular processes as well as its therapeutic potentials are emphasized..